A critical review on the translational journey of cardioprotective therapies!. (1st October 2016) - Rossello, Xavier; Yellon, Derek M.
Abstract: The failure to translate novel cardioprotective therapies tested in pre-clinical studies into the clinical setting for patient benefit can be attributed to a number of factors at different stages of the research process. This review focuses on the evidences and the gaps with regard to the translational journey of cardioprotective interventions. Gaps are classified into 3 main groups: 1) those related to pre-clinical studies, 2) those associated with the validation of infarct size as a good surrogate and 3) those based on design and interpretation of randomized clinical trials on cardioprotection. Addressing these gaps might increase the chances to successfully translate cardioprotective therapies into improving both post-STEMI heart failure and cardiovascular death rates. Highlights: Cardioprotective therapies have not been translated into clinical benefits so far. Gaps regarding both preclinical and clinical study design need to be addressed. Co-morbidities and concomitant medication are major confounding factors. There is still room to improve both post-STEMI heart failure and mortality rates.